The sacred wilderness of pastoral ministry : preparing a people for the presence of the Lord - Rohrer, David, 1957- (Hyderabad, India Authentic Books, 2013)
"Pastors often find themselves struggling to survive in the wilderness of the contemporary church scene. How do they remain faithful in light of the marginalization of organized religion, denominational strife, rapid demographic change, falling numbers and a general malaise among church members? Many pastors feel helpless, others hopeless. Sociologists and pollsters diagnose the problem but can't seem to come up with a solution. Is there hope? Author and pastor David Rohrer believes there is. John the Baptist also lived in the wilderness, yet crowds journeyed there to hear him. Why? Because John 'affirmed what people already knew: that they were in desperate need of something more than the mundane practices of a religion that had been cut off from its source of life.' John called people to remember their covenant relationship with God, which was established in the wilderness, and to let God guide them once again across the Jordan and into the Promised Land. Pastors, says Rohrer, 'don't primarily exist to build and maintain the institution of the church. We exist to do a particular work through the church. In short, we don't simply have an institution to create, refine or maintain; we have a gospel to preach.' John's prophetic voice prepared hearts to be receptive to Christ's work among them, to be transformed by the power of God. Herein lies hope! Using illustrations from everyday church life and decades of ministry experience, Rohrer carefully crafts a lively and realistic pastoral theology for ministry in the sacred wilderness. If you are a new pastor you have a sure guide here. If you are a veteran preacher you'll find just the refresher course you need to invigorate your ministry."--Publisher's description.
Consolation: making ready a people versus being the parson -- Call: God's work versus our vision -- Covenant: proclaiming the good news versus managing the message -- Commission: accepting our office versus cultivating loyalty -- Context: inhabiting a place versus propagating a program -- Confrontation: inviting awareness versus administering anesthesia -- Conflict: trusting truth versus fearing instability -- Confusion: risking doubt versus denying dissonance -- Confidence: receiving God's blessing versus seeking approval -- Postscript: it's not about you -- or is it?
Includes bibliographical references and indexes.
Keywords: Pastoral theology